2012
DOI: 10.1111/jace.12063
|View full text |Cite
|
Sign up to set email alerts
|

Direct Coagulation Casting of Alumina Suspension via Controlled Release of High Valence Counterions from Thermo‐sensitive Liposomes

Abstract: Thermo‐sensitive liposomes were prepared using reverse phase evaporation method using natural lipid egg phosphatidylcholine (EPC) and cholesterol (CH). Inorganic salts containing high valence counterions (HVCI) are encapsulated by the liposomes. The phase transition temperature of the liposome is at 38°C with 50 wt% addition of cholesterol. The encapsulation rate of liposomes reaches 85% for high valence anion (SO42−) and 55% for high valence cation (Ca2+). The liposomes are introduced into ceramic colloidal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…[66] Lipophilic drugs are encapsulated in the hydrophobic region of the lipid bilayers of liposomes, whereas hydrophilic drugs are loaded into their interior aqueous compartments. [67][68][69][70] Numerous methods for preparing drug-loaded liposomes have been developed; they include thin film hydration, [71,72] emulsion, [51,73] sonication, [68,74] and extrusion. [75,76] The size of as-prepared liposomes normally ranges from 100 nm to several microns, and may influence their uptake by enterocytes; smaller liposomes are generally taken up by enterocytes in greater quantities.…”
Section: Liposomesmentioning
confidence: 99%
“…[66] Lipophilic drugs are encapsulated in the hydrophobic region of the lipid bilayers of liposomes, whereas hydrophilic drugs are loaded into their interior aqueous compartments. [67][68][69][70] Numerous methods for preparing drug-loaded liposomes have been developed; they include thin film hydration, [71,72] emulsion, [51,73] sonication, [68,74] and extrusion. [75,76] The size of as-prepared liposomes normally ranges from 100 nm to several microns, and may influence their uptake by enterocytes; smaller liposomes are generally taken up by enterocytes in greater quantities.…”
Section: Liposomesmentioning
confidence: 99%
“…15,16 Xu et al proposed the coagulation of alumina suspension via controlled release of high valence counter ions. 17,18 In the methods described above, all suspensions used in DCC process are electrostatic or electrosteric stable. In the process of coagulation, the surface charge of particle and zeta potential are decreased by adjusting pH to isoelectric point (IEP) or increasing ionic strength to compress electric double layer.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, most DCC systems do not involve toxicants as gel‐casting does. Thus, DCC has been widely applied in the preparation of various dense ceramic components with high performance and complex shapes . Up to now, however, little research has been reported on the preparation of porous ceramics via DCC method due to their poor green strength (~100 kPa) of wet‐coagulated samples and easy cracking in green bodies.…”
Section: Introductionmentioning
confidence: 99%